Politik Hukum dalam Undang-Undang No. 38 Tahun 1999 Tentang Pengelolaan Zakat Perspektif Maqasid al-Risalah - Muhammad Solikhudin; Oktaria Ardika Putri (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2020)
This paper tries to explain the legal policy of the law carried out by the Indonesian government about zakat which is an obligation for capable Muslims as a manifestation of human empathy to others in need. Zakat has a noble goal, namely to alleviate poverty and eliminate social inequality in society. This objective is in line with one of the objectives of the Indonesian government which has been mandated in the opening of the 1945 Constitution, namely to advance public welfare. Thus, the management of zakat in Indonesia will be better, if implemented by the government, given that zakat is a very potential source of funds that can be used for public welfare for all Indonesian people. This article explains the process of formulating zakat laws in Indonesia, the substance of Islamic law in zakat, and the purpose of the Law (maqa>sid al-risa>lah) about zakat in Indonesia, so that readers can fully comprehend the purpose of zakat law.